2021
DOI: 10.1186/s40468-021-00134-5
|View full text |Cite
|
Sign up to set email alerts
|

The affectability of writing assessment scores: a G-theory analysis of rater, task, and scoring method contribution

Abstract: The present study attempted to to investigate  factors  which affect EFL writing scores through using generalizability theory (G-theory). To this purpose, one hundred and twenty students participated in one independent and one integrated writing tasks. Proceeding, their performances were scored by six raters: one self-rating,  three peers,-rating and two instructors-rating. The main purpose of the sudy was to determine the relative and absolute contributions of different facets such as student, rater, task, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The answer to such a question could be found in classical test theories but in generalizability analysis of the test results. Usually in the administration of high-stakes and standardized tests the test administration context, the number of items, and the same scoring procedure have kept stable in order to eliminate any source of construct irrelevant variance (Khodi, 2021). This could be problematic due to two reasons: first, there is no intention to revise and improve the test quality by the test administrators and developers; second, keeping these conditions stable without examining the relative and absolute contribution they have would not be really insightful and helpful in reliability assessment.…”
Section: Optimization and Generalizability Analysis Of The Testmentioning
confidence: 99%
“…The answer to such a question could be found in classical test theories but in generalizability analysis of the test results. Usually in the administration of high-stakes and standardized tests the test administration context, the number of items, and the same scoring procedure have kept stable in order to eliminate any source of construct irrelevant variance (Khodi, 2021). This could be problematic due to two reasons: first, there is no intention to revise and improve the test quality by the test administrators and developers; second, keeping these conditions stable without examining the relative and absolute contribution they have would not be really insightful and helpful in reliability assessment.…”
Section: Optimization and Generalizability Analysis Of The Testmentioning
confidence: 99%
“…The process of rating writing tasks may also be affected by other factors such as the type of task or the scoring method. Recently, Khodi (2021) in a G-theory analysis of rater, task, and scoring method examined the affectability of writing assessment scores. Using various raters, tasks, and scoring methods, he found that to reach maximum generalizability, students should take two writing tasks and their performance should be evaluated by at least four raters using at least two scoring methods.…”
Section: Process Of Rating Writing Tasksmentioning
confidence: 99%
“…The characteristics of raters in writing assessment are the idiosyncrasy that can be sought in the cognitive, attitudinal, and background variables. These factors are affected by raters’ appropriate education, training, and prior experience (Khodi, 2021 ; Kim & Lee, 2015 ; Rahayu, 2020 ). To prevent assigning inconsistent scores, concentrating properly and exclusively on evaluation of examinee’ writing performance during the rating process, and applying appropriate rating procedures, raters should receive professional training.…”
Section: Introductionmentioning
confidence: 99%